2017
DOI: 10.12659/msm.901309
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alcohol Consumption and Metabolic Syndrome in a Community-Based Cohort of Korean Adults

Abstract: BackgroundThe relationship between alcohol consumption and metabolic syndrome (MetS) remains controversial. This study investigated the relationship between alcohol consumption and MetS components and prevalence.Material/MethodsWe analyzed 10 037 subjects (3076 MetS and 6961 non-MetS) in a community-based cohort.MetS was defined according to the ATP III Guidelines. Subjects were divided according to amount of alcohol consumption; non-drinker, very light (0.1–5.0 g/day), light (5.1–15.0 g/day), moderate (15.1–3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 28 publications
1
26
0
5
Order By: Relevance
“…In the present study, MS onset was associated with smoking in women in their 20s and 30s, and eating speed in women in their 30s, associated with physical activity, eating speed, and alcohol intake in men in their 20s and 30s, and smoking in men in their 40s. Many previous studies reported that MS onset is associated with smoking, 29 eating speed, 30 alcohol intake, 31 and physical activity. 32 Other poor lifestyle factors are not significantly correlated with MS onset in young adults, but the impact of each poor lifestyle could not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, MS onset was associated with smoking in women in their 20s and 30s, and eating speed in women in their 30s, associated with physical activity, eating speed, and alcohol intake in men in their 20s and 30s, and smoking in men in their 40s. Many previous studies reported that MS onset is associated with smoking, 29 eating speed, 30 alcohol intake, 31 and physical activity. 32 Other poor lifestyle factors are not significantly correlated with MS onset in young adults, but the impact of each poor lifestyle could not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of metabolic syndrome was shown to be two to fourfold higher in men than in women . Therefore, women have a healthy lifestyle, including less smoking and alcohol consumption, than men . Epigenetics also affects the occurrence of hyperlipidemia and diabetes mellitus in later life.…”
Section: Discussionmentioning
confidence: 99%
“…17 Therefore, women have a healthy lifestyle, including less smoking and alcohol consumption, than men. 18 Epigenetics also affects the occurrence of hyperlipidemia and diabetes mellitus in later life. This is another reason why we focused on women in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…One prospective study found a linear increase in metabolic syndrome risk with an increase in alcohol consumption [23]. Yet, another study indicated that alcohol drinking (0.1-5.0 g/day) contributed to decrease prevalence of MetS and components, including triglyceride and HDL cholesterol [24]. In order to explain the causal relationship between alcohol consumption and the metabolic syndrome and its components, prospective studies might be necessary.…”
Section: Discussionmentioning
confidence: 99%